On the wisdom of America - Yutang, Lin (J. Day, 1950)
These thought-provoking teachings from respected Native American leaders and thinkers provide a connection with the land, the environment, and the simple beauties of life. This collection of writings from revered Native Americans offers timeless, meaningful lessons on living and learning.